The Seven Deadly Sins? Issues in Clinical Practice and Supervision for Humanistic and Integrative Practitioners. - Kearns, A. (Anne) (Karnac Books, 2005)
This book aims to make more accessible some concepts from the world of psychoanalysis, self-psychology and affective neuroscience, as well as commenting on the challenge of working "in the real world". This is achieved by offering an integrative and anecdotal perspective on issues that have been generally un- or under-explored in trainings, using case studies as illustration.